System of Supervision and Control of Syariah Banking - Elsa Susanti; Rozi Andrini; M. Israr Fathoni (Yayasan Pendidikan Islam Al-Matani, 2024)
In Indonesia, the supervision and management of Islamic banking is very important to ensure that the activities of Islamic banks comply with relevant laws. DPS should strictly supervise Islamic banking products given the expansion of this sector and the services offered. DPS is in charge of assessing compliance with sharia law. In addition, effective risk management is key in withstanding challenges and mitigating compliance, liquidity, and credit risks. This system aims to increase public trust in banking, in addition to protecting sharia consumers as a sustainable and ethical financial alternative. Thus, good supervision is expected to encourage stable growth in Indonesia's Islamic banking industry. This study aims to investigate the supervision and management structure of Islamic banking in Indonesia.